Immunological, chemical and clinical aspects of exposure to mixtures of contact allergens - Bonefeld, Charlotte M.; Geisler, Carsten; Gimenez-Arnau, Elena; Lepoittevin, Jean-Pierre; Uter, Wolfgang; Johansen, Jeanne D. (Contact Dermatitis, 2017)
Allergic contact dermatitis is one of the most frequent forms of skin inflammation. Very often, we are exposed to mixtures of allergens with varying potencies, doses/areas, and exposure times. Therefore, improved knowledge about immune responses to combinations of contact allergens is highly relevant. In this article, we provide a general introduction to immune responses to contact allergens, and discuss the literature concerning immune responses to mixtures of allergens. According to the existing evidence, increased responses are induced following sensitization with combinations of allergens as compared with single allergens. The response to a mixture of allergens can be both additive and synergistic, depending on the dose and combination of allergens. Importantly, sensitization with combinations of either fragrance allergens or metal salts can result in increased challenge responses to specific allergens within the mixture. Taken together, the immune responses to mixtures of allergens are complex, and further studies are required to obtain the necessary knowledge to improve consumer safety.
EVALuna2:34180